2016
DOI: 10.1136/jclinpath-2015-203538
|View full text |Cite
|
Sign up to set email alerts
|

BCR-ABL1expression, RT-qPCR and treatment decisions in chronic myeloid leukaemia

Abstract: Variation between individuals in expression of BCR-ABL1 can materially affect interpretation of the RT-qPCR when this test is used to make decisions on treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In addition, we and others have compared the quantification of BCR-ABL in genomic DNA and RNA in serial samples and have shown that individual patients may have consistently higher or lower expression of BCR-ABL mRNA for a given number of CML cells. 47,48 This interindividual difference results in a measurement bias whereby RQ-PCR may underestimate the level of residual disease in some patients. Although genomic Q-PCR for BCR-ABL is not widely available, it is a promising research tool to elucidate the relationship between MRD and TFR outcome.…”
Section: Areas Of Future Investigationmentioning
confidence: 99%
“…In addition, we and others have compared the quantification of BCR-ABL in genomic DNA and RNA in serial samples and have shown that individual patients may have consistently higher or lower expression of BCR-ABL mRNA for a given number of CML cells. 47,48 This interindividual difference results in a measurement bias whereby RQ-PCR may underestimate the level of residual disease in some patients. Although genomic Q-PCR for BCR-ABL is not widely available, it is a promising research tool to elucidate the relationship between MRD and TFR outcome.…”
Section: Areas Of Future Investigationmentioning
confidence: 99%
“…MR 5.0 at all (Figure S2C). In any cases, the consideration of the detectability of the transcript was not statistically significant.…”
mentioning
confidence: 95%
“…The reverse transcription quantitative polymerase chain reaction (RT-qPCR) is considered as the most sensitive, reliable and accurate technique to analyze differential gene expression at the messenger RNA (mRNA) level [1, 2]. Nevertheless, performing the experimental procedures will introduce a variety of potential errors, amongst which pipetting errors, starting material quality variations, differences in mRNA extractions, errors in sample quantifications, altered reverse transcription efficiencies and cDNA sample loading differences [3].…”
Section: Introductionmentioning
confidence: 99%